Ageism combating strategies in oral healthcare: A systematic review - Mendes, Mariana Sarmet Smiderle [UNESP] (2025)
Purpose: The aim of this study is to investigate the existing evidence regarding the effectiveness of strategies aimed at combating ageism against older adults among dental students. Methods: A systematic review was performed following preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines to identify articles from seven electronic databases: MEDLINE via the PubMed interface, Embase, Age-Line, Scopus, Web of Science, CINAHL, and Cochrane. Results: Among twenty-four references reporting on ageism among oral health care providers and/or students, only two reported on the outcomes of strategies for combating ageism at dental schools, with a 12-year gap between them. Both studies showed that non-geriatric-specific clinical activities during dental school might reduce ageism among students. Notably, each article used a different tool to assess ageism. Conclusion: Although the dental literature calls for action to reduce ageism in many published articles, there is a need for more studies evaluating the outcomes of strategies to combat ageism in oral healthcare.